'Welcome to the EPL': analysing the development of football tourism in the English Premier League. (4th July 2022) - Tobar, Felipe; Ramshaw, Gregory
ABSTRACT: In the past two decades, English Premier League (EPL) top clubs have targeted broader touristic markets, particularly tourists looking to experience behind-the-scenes venue tours, venue-based club museums, and match-day experiences in the stands and corporate boxes. While the increasing touristic appeal of EPL grounds has positive financial outcomes for both club and community, several drawbacks have been identified, particularly by local supporters, including tourists as being detrimental to the match atmosphere, tourists exhibiting annoying behaviour, and touristic demand driving up ticket prices. The football literature covering the development and transformations of the EPL since its creation in 1992 has mainly highlighted its transnational nature through foreign players, owners, managers, and coaches. This paper explores the development of football tourism within the EPL, while highlighting issues such as over-tourism, place-displacement, and cultural sustainability at football grounds. The EPL's potential challenges concerning Brexit and COVID-19 impacts on tourism are also addressed.